Becoming a family counselor : - Blume, Thomas W. (J. Wiley, 2006)
Becoming a Family Counselor sets a new standard for family therapy texts. Working from a broad historical orientation, it focuses on the common themes that reappear across various theoretical approaches and connects family practice with individual approaches. Crossing boundaries of generation, gender, race, and culture, this useful introduction presents current thinking related to today's practice issues.